2008
DOI: 10.1007/s11064-008-9730-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acrylamide on the Nervous Tissue Antioxidant System and Sciatic Nerve Electrophysiology in the Rat

Abstract: To investigate the time-dependent effects of acrylamide (ACR) on the antioxidative status in rat nerve tissues, adult male Wistar rats were given ACR (40 mg/kg, i.p., 3 times/week) for 2, 4, 6 and 10 weeks, respectively. The time-dependent changes of the lipid peroxidation (malondialdehyde, MDA) and antioxidative status (glutathione, GSH; glutathione peroxidase, GSH-Px; glutathione reductase, GR; superoxide dismutase, SOD and anti-reactive oxygen species, anti-ROS) in nerve tissues were investigated. The elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 35 publications
9
84
0
1
Order By: Relevance
“…However, the changes in antioxidant structures following exposure to ACR have not been clarifi ed yet. In a study about the effects of ACR on nerve tissues and antioxidant system, it was observed that while MDA level signifi cantly increased, GSH level signifi cantly decreased (15). Smoking is one of the most striking risk factors for lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the changes in antioxidant structures following exposure to ACR have not been clarifi ed yet. In a study about the effects of ACR on nerve tissues and antioxidant system, it was observed that while MDA level signifi cantly increased, GSH level signifi cantly decreased (15). Smoking is one of the most striking risk factors for lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to AA induces a significant reduction in GSH concentration in different cells [7][8][9] and contributed to the onset of oxidative stress conditions, which can adversely affect cell function and potentially lead to cell damage and death [10]. However, while previous studies have documented the link between AA-induced oxidative stress and cytotoxicity in several tissues [3][4][5], to date the potential impact of AA on the integrity of gastrointestinal tract, the primary organ in contact with food, is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…One group examined the time-dependent effects acrylamide had on the antioxidative stress in rat nerve tissues. With increased concentrations injected into rats over a few weeks, decreases were found in both CAP duration and CAP amplitude [116]. Furthermore, they found that acrylamide may be associated with an increase in lipid peroxidation and reduction of the anti-oxidative capacity.…”
Section: Sciatic Nerve As a Cns Proxymentioning
confidence: 98%